A Validated UV Spectroscopic Method for Simultaneous Determination of Benzil and Benzophenone Impurities in Phenytoin Sodium - Korde, Pooja; Sanjay Pai, P.N. (Asian Journal of Chemistry, 2014)
A simple, accurate, precise, economical and reproducible UV spectrophotometric method has been developed for the simultaneous determination of benzophenone and benzil impurities in phenytoin sodium. The method employs formation and solving of simultaneous equation using 222, 257 and 263 nm as the analytical wavelengths. Method was found to be precise and was reproducible as shown from the validation studies.